The archive incarnate : the embodiment and transmission of knowledge in science fiction - Hurtgen, Joseph, 1981- (Critical explorations in science fiction and fantasy, 2018)
"We live in an information economy, data ever at our fingertips. In the pages of science fiction, powerful entities--governments and corporations--seek to use this archive to control society, enforcing conformity or turning citizens into passive consumers. Opposing them are protagonists fighting to liberate the collective mind from those who would enforce top-down control"--